The effect of unhealthy dietary habits on the incidence of dental caries and overweight/obesity among Egyptian school children (A cross-sectional study) - Mahmoud, Sara Ahmed; El Moshy, Sara; Rady, Dina; Radwan, Israa Ahmed; Abbass, Marwa M. S.; Al Jawaldeh, Ayoub (Frontiers in Public Health, 2022)
Background Obesity and dental caries are public health problems in Egypt. Factors such as unhealthy diet, poor oral hygiene, and physical inactivity can play a major role in both problems. This study was carried out to illuminate the mutual unhealthy dietary risk factors associated with the incidence of both health conditions. Methods Between 1 October 2020 and 1 July 2021, 369 Egyptian children (5–10 years) were examined. Dental status was assessed using decayed, missing/extracted, and filled tooth indices (dmft, deft, and DMFT) for deciduous, mixed, and permanent dentitions, respectively. Moreover, the lifestyle, food habits, and body mass index (BMI) were recorded. Results A total of 342 (93.7%) of the included subjects suffered from caries, and only 27(7.3%) were caries-free. Based on BMI percentiles, 247 (66.9%) of the youngsters were overweight/obese, while 122 (33.1%) had normal weight. The mean dmft was 6.9 (±4.6), deft 4.2 (±3.3), and DMFT 0.1 (±1.7). In the primary dentition, a significant positive correlation was detected between dmft and BMI, legumes, sweetened milk and juice, soft drinks, and desserts, while a significant negative correlation was detected between dmft/deft, meat/poultry/fish, fresh fruits, and vegetables. A significant positive correlation was detected between deft and BMI, sweetened milk and juice, ice cream, candies, and crackers. In the permanent dentition, a significant positive correlation was detected between age, soft drinks, sweetened juice, desserts, and DMFT, while a significant negative correlation was detected with fresh fruits and vegetables. BMI was significantly negatively correlated with a healthy lifestyle, meat/poultry/fish consumption, and fresh fruits and vegetables while positively correlated with legumes, ice cream, soft drinks, granulated sugars, desserts, fast food, and caffeinated drinks. Conclusion Overweight/obesity was positively correlated with primary dentition dental caries. Desserts (sweetened snacks) and soft drinks could be the common risk factors associated with high caries and overweight/obesity incidence among Egyptian school children; conversely, consumption of fruits and vegetables could hinder both health conditions. Moreover, sweetened juices were associated with primary and permanent dental caries.